Numerical Investigations on Heat Flow of Nanofluids in Ribs Tube Configurations - Salman, Sami D.; Abd Alsaheb, Ramzi Ata (Al-Khwarizmi Engineering Journal, 2017)
AbstractIn this paper presents two dimensional turbulent flow of different nanofluids and ribs configuration in a circular tube have been numerically investigation using FLUENT 6.3.26. Two samples of CuO and, ZnO nanoparticles with 2% v/v concentration and 40 nm as nanoparticle diameter combined with trapezoidalribs with aspect ratio of p/d=5.72 in a constant tube surface heat flux were conducted for simulation. The results showed that heat flow as Nusselt number for all cases raises with Reynolds number and volume fraction of nanofluid, likewise the results also reveal that ZnO with volume fractions of 2% in trapezoidal ribs offered highest Nusselt number at Reynolds number of Re= 30000.Keyword: Heat transfer augmentation, Friction factor, Thermal performance factor, Ribs configuration, CFD simulation, Fluent.